Interactive social pragmatic intervention and responsive engagement (INSPIRE): An intervention program to facilitate social skills among toddlers with autism - Ramandeep Kaur (MethodsX)
Pragmatic skills—how children use language in social situations—begin to develop early in life and are important for toddlers as they learn to communicate their needs, build relationships, and explore their environment. While many toddlers naturally pick up these skills through everyday interactions, there is growing recognition that some may benefit from early support. However, targeted intervention strategies for enhancing pragmatic development in toddlers are still not widely explored. The primary objective of this study was to develop a comprehensive intervention program designed to foster pragmatic skills among toddlers who are diagnosed with Autism. The overall process of development of this program, was conducted in three distinct phases. The first phase focused on creating various illustrative stories along with activities targeting specific pragmatic domains. In the second phase, an expert validation process was carried out, engaging a team of experienced speech-language pathologists, and other professionals along with parents of children with Autism. As a result, the study produced a Toolkit named INSPIRE-Core for toddlers between 1 and 3 years. The third phase focused on standardization of this toolkit by parental implementation of this program on 50 children with specific inclusion and exclusion criteria, within home environments. Overall, the study demonstrated that the intervention program served as an effective and structured resource for parents, supporting systematic planning and implementation of pragmatic language interventions. • A three-phase design was employed to systematically develop and validate the intervention program, targeting pragmatic skills in children with language delays. • Expert validation ensured the program's robustness, involving speech-language pathologists, other professionals and parents of children with autism. • Standardization was achieved through implementation on a stratified sample of 50 children with autism, categorized by language age and trained within home environments.